Determinasi Pengaruh Keputusan Investasi Saham dengan Perilaku Keuangan Sebagai Variabel Moderasi - Faradisa, Assyfa; Maslichah, Maslichah; Fakhriyyah, Dewi Diah (e_Jurnal Ilmiah Riset Akuntansi, 2026)
The research was done on purpose to help analyzing the influence of financial technology, financial literacy, and also risk perception on decisions of stock investment and also financial behavior acts as a moderating variable of those student members of the Indonesia Stock Exchange (IDX) Investment Gallery in Malang City. The background is the increasing participation of young investors that has not been fully accompanied by the quality of rational investment decision-making. This study applied such a quantitative approach by applying primary data taken through questionnaires from 106 respondents taken by purposive sampling technique. Data were analyzed by applying SEM–PLS method. The outcomes indicate that financial technology, financial literacy, and also risk perception give such a positive influence toward stock investment decisions, as does financial behavior. However, in its role as a moderating variable, financial behavior weakens the influence of these three variables on investment decisions. These findings support Behavioral Finance Theory and Planned Behavior Theory, help in emphasizing that decisions of students’ investment are made by an interaction of technological factors, financial understanding, and rational behavioral control.Keywords: Stock investment decision, financial technology, financial literacy, risk perception, financial behavior, SEM-PLS.